2019
DOI: 10.1111/jvh.13129
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E during pregnancy: Maternal and foetal case‐fatality rates and adverse outcomes—A systematic review

Abstract: Abbreviations: CFR, case-fatality rate; FHF, fulminant hepatic failure; HEV, hepatitis E virus; IQR, interquartile range; LBW, low birth weight; NOS, Newcastle-Ottawa Scale;PRISMA, preferred reporting items for systematic reviews and meta-analysis; PROM, premature rupture of membranes. AbstractHepatitis E virus infection during pregnancy can have severe consequences for mother and child, such as vertical transmission, fulminant hepatic failure, even foetal or maternal mortality. The aim of this systematic revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 28 publications
(76 reference statements)
5
36
0
1
Order By: Relevance
“…A 2019 systematic review including a total of 1,338 pregnant women with hepatitis E showed a 45% risk of fulminant hepatic failure, a median maternal CFR of 26% and a median fetal CFR of 33%. Other obstetric complications were not consistently reported in the included articles but data from four studies suggest an increased risk of postpartum hemorrhage, ranging from 13.6 to 30% ( 28 ). There are no proven drug therapies for hepatitis E (ribavirin, which has shown equivocal benefits in small case series, is contraindicated in pregnancy) and the only available vaccine for prevention of hepatitis E is not manufactured or licensed outside China ( 28 ).…”
Section: Acute Viral Infections That Cause Severe Maternal Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…A 2019 systematic review including a total of 1,338 pregnant women with hepatitis E showed a 45% risk of fulminant hepatic failure, a median maternal CFR of 26% and a median fetal CFR of 33%. Other obstetric complications were not consistently reported in the included articles but data from four studies suggest an increased risk of postpartum hemorrhage, ranging from 13.6 to 30% ( 28 ). There are no proven drug therapies for hepatitis E (ribavirin, which has shown equivocal benefits in small case series, is contraindicated in pregnancy) and the only available vaccine for prevention of hepatitis E is not manufactured or licensed outside China ( 28 ).…”
Section: Acute Viral Infections That Cause Severe Maternal Diseasementioning
confidence: 99%
“…The World Health Organization estimates that sepsis accounts for 10.7% of maternal deaths globally ( 33 ) and there is evidence of a particular vulnerability to acute viral infection. For example, pregnant women suffered disproportionately high mortality rates in the influenza pandemics of 1918, 1957, and 2009 ( 34 36 ), and hepatitis E, typically a mild and self-limiting illness, has a 26% case-fatality rate in pregnant women ( 28 ). These disparities are likely to arise from a combination of immunological, hormonal, and physiological adaptations that are specific to pregnancy ( 37 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our study is not powered to directly evaluate perinatal and maternal death, because of the low rates of these outcomes in Matlab. However, given the substantial evidence linking maternal and perinatal mortality to HEV disease in pregnancy,2 demonstration of vaccine protection against confirmed HEV disease in pregnancy will provide strong evidence that vaccination is likely to prevent maternal and perinatal deaths.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Hepatitis E virus (HEV) is an enteric RNA virus causing outbreaks or endemics in developing countries with poor sanitation and is one of the leading causes of acute hepatitis worldwide 1. Pregnant women are particularly vulnerable to HEV infection, with a high rate of maternal mortality, miscarriage, premature delivery and stillbirth 2…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis shows that the pooled case-fatality risk for pregnant mothers can be as high as 26 % for acute HEV infection [109]. Other pregnancy complications include preterm labour (50 %) and prelabour rupture of membranes (10 %), while postpartum haemorrhage was reported in 13.6-30 % [112].…”
Section: Hepatitis Ementioning
confidence: 99%